Madrasah Strategic Management in Improving The Quality of Human Resources - Basri, Basri; Ridwan, Muhamad; Maudin, Maudin; Asykur, Muamar (JURNAL AL-TANZIM, 2022)
Human resource management for madrasah has a vital role given the dynamics of diversity in motives, work orientation, background experience, competence, culture, workforce diversity, and globalization. This research aims to understand the strategic management of madrasah in improving the quality of Islamic human resources at MAN 2 Makassar City. This study uses a qualitative case study type method. The data collection technique was carried out through participant observation, in-depth interviews, and documentation. Before the researcher analyzed the data, the data was first processed (data processing), followed by the editing process, coding, data presentation, concluding. The results of the study indicate that the strategic management of madrasah in improving the quality of Islamic human resources is carried out through internal and external environmental analysis, strategy formulation, implementation of quality-based management that focuses on customer satisfaction focus and continuous improvement, internalization of Islamic teachings values and continuous evaluation.